The Neglected Integration Crisis: France, Germany and Lacking European Co-operation During the 1973/1974 Oil Shock - Lucas Schramm (JCMS: Journal of Common Market Studies, 2023)
When does European co-operation and (further) integration not happen in the face of a major integration crisis? When do France and Germany not emerge as regional stabilizers, forging and uploading bilateral compromises to the European level? By developing a combined theoretical framework based on liberal intergovernmentalism and leadership approaches, this article analyses the European Economic Community's (EEC) reaction to the 1973/1974 oil crisis. Despite some favourable conditions, differences in domestic energy markets and relations with Arab oil-producing countries complicated member state co-operation. In turn, divergent economic philosophies and foreign policy priorities prevented France and Germany from filling the European leadership vacuum. As a consequence, the EEC did not find a unified stance on the Arab oil embargo, subordinated itself to US-American dominance and undermined its common market via export restrictions for oil. The findings suggest that without minimum convergent member state preferences or compensating regional leadership, European integration and today's European Union risk stalling or even disintegrating.
Keywords: 330; European integration; France; Germany; leadership; liberal intergovernmentalism; oil crisis